2018
DOI: 10.1021/jacs.8b08254
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Control of Covalency Effects Related to the Active Sites of Molybdenum Enzymes

Abstract: A multitechnique spectroscopic and theoretical study of the CpM(benzenedithiolato) (M = Ti, V, Mo; Cp = η-CH) series provides deep insight into dithiolene electronic structure contributions to electron transfer reactivity and reduction potential modulation in pyranopterin molybdenum enzymes. This work explains the magnitude of the dithiolene folding distortion and the concomitant changes in metal-ligand covalency that are sensitive to electronic structure changes as a function of d-electron occupancy in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The lower Φ of Fe NPs @Fe SAs NC than that of Fe NPs /CN is caused by the enriched electron density on the Fe–N–C interface, confirming a lower energy barrier for electron transfer from the internal zero-valent iron particles. 40 Moreover, as compared to Fe NPs /CN, Fe NPs @Fe SAs NC demonstrated a smaller semicircle in the Nyquist plot than that of Fe NPs /CN (Fig. 3(e)), indicating a lower electrochemical impedance and higher electron-transfer kinetics in the redox reactions.…”
Section: Resultsmentioning
confidence: 93%
“…The lower Φ of Fe NPs @Fe SAs NC than that of Fe NPs /CN is caused by the enriched electron density on the Fe–N–C interface, confirming a lower energy barrier for electron transfer from the internal zero-valent iron particles. 40 Moreover, as compared to Fe NPs /CN, Fe NPs @Fe SAs NC demonstrated a smaller semicircle in the Nyquist plot than that of Fe NPs /CN (Fig. 3(e)), indicating a lower electrochemical impedance and higher electron-transfer kinetics in the redox reactions.…”
Section: Resultsmentioning
confidence: 93%
“…Investigations of Mo dithiolene compounds by electronic absorption, resonance Raman, and EPR spectroscopies showed that S → Mo charge transfer bands dominate the visible spectrum and that there is substantial delocalization of spin density onto the S atoms of the dithiolene. Recent comprehensive studies of bent metallocene-dithiolene compounds have shown that low-energy ligand fold distortions arise from a pseudo-Jahn-Teller (PJT) effect, which involves vibronic coupling of the electronic ground state with electronic excited states to control metal-ligand covalency [ 60 ] ( Section 5 ). This vibronic coupling process may play critical roles in the catalytic cycles of pyranopterin Mo and W enzymes by dynamic and/or static modulation of redox potentials and providing a superexchange pathway for electron transfer through the PDT framework.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of MCD, electronic absorption, electron paramagnetic resonance, resonance Raman, and photoelectron spectroscopies has been used in conjunction with theory to reveal vibrational control of metal-ligand covalency in a series of Cp 2 M(bdt) complexes (M = Ti, V, Mo; Cp = η 5 -C 5 H 5 ) [ 60 ] ( Figure 4 ). The work is important because it has allowed for a detailed understanding of how redox orbital electron occupancy (Ti(IV) = d 0 , V(IV) = d 1 , Mo(IV) = d 2 ,) affects the nature of the M-dithiolene bonding scheme at parity of the ligand set and at parity of charge.…”
Section: Vibrational Control Of Covalencymentioning
confidence: 99%
“…MCD spectroscopy has been used to probe the electronic structure of chicken sulfite oxidase that was poised in the catalytically relevant [Mo(V):Fe(II)] state [ 145 , 147 ] ( Figure 6 , middle). No charge transfer transitions were observed at energies below ~17,000 cm −1 and this was interpreted to result from a reduction in S ip –S op orbital mixing and S op –Mo d(xy) covalency, in addition to a small dithiolene fold angle [ 130 , 145 , 147 , 148 , 149 , 150 , 151 ]. A band at 22,250 cm −1 was observed as a positive C-term and assigned as a S σ (cysteine)→Mo(xy) LMCT transition.…”
Section: Magnetic Circular Dichroism Spectroscopymentioning
confidence: 99%